2011
DOI: 10.1177/1545109711423445
|View full text |Cite
|
Sign up to set email alerts
|

Nevirapine-Associated Hepatotoxicity and Rash among HIV-Infected Pregnant Women in Kenya

Abstract: Nevirapine use but not CD4 count ≥250 cells/mm(3) was associated with hepatotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Two studies with CD4 cut-offs of 500 29 Fourteen studies were reviewed, including a total of 2 663 participants (Table 2). 4,5,[27][28][29][30][31][32][33][34][35][36][37][38] One study was funded by the NVP manufacturer Boehringer Ingelheim. 30 The studies, mostly undertaken between 2001 and 2006, were predominantly observational with participant numbers ranging from 17 to 703.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies with CD4 cut-offs of 500 29 Fourteen studies were reviewed, including a total of 2 663 participants (Table 2). 4,5,[27][28][29][30][31][32][33][34][35][36][37][38] One study was funded by the NVP manufacturer Boehringer Ingelheim. 30 The studies, mostly undertaken between 2001 and 2006, were predominantly observational with participant numbers ranging from 17 to 703.…”
Section: Resultsmentioning
confidence: 99%
“…Participants with hepatitis B or C infection were excluded from 2 studies, 4,27 whereas 7 studies reported the prevalence of hepatitis co-infection. [28][29][30]34,[36][37][38] NVP was initially commenced at 200 mg daily for 14 days in all women. The CD4 cut-off was 250 cells/µl for toxicity analyses in all studies, except for one (CD4 cut-off of 200 cells/ µl).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Las reacciones tóxi-cas pueden aparecer entre los 10 y los 280 días de iniciado el tratamiento (23)(24)(25)(26). La hepatotoxicidad se ha presentado en pacientes con edad entre los 18 y 45 años (21, 24-27), con elevación de las transaminasas y rash (23,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Valoración De La Aparición De Hepatotoxicidadunclassified